Resources for Mechanical Mechanism for Fighting Plants - R.Z Salieva; Z.A Turgunov (Universitas Muhammadiyah Sidoarjo, 2019)
Currently, agricultural crops around the world are affected by pests and weeds. Chemical combat against them presents some difficulty in the field. This appliance facilitates the use of chemicals against diseases, weeds and especially pests. This is because the equipment sprayed the plant from the bottom.